Calcium thin film growth on a cyano-substituted poly(p-phenylene vinylene): Interface structure and energetics - Sharp, J. C.; Bebensee, Fabian; Baricuatro, J. H.; Steinrück, Hans-Peter; Gottfried, J. Michael; Campbell, C. T. (Journal of Physical Chemistry C, 2013)
The adsorption of Ca on poly[2-(2-ethylhexyloxy)-5-methoxy-1,4-phenylene cyanovinylene] (MEH-CN-PPV) at 130 and 300 K has been studied by adsorption microcalorimetry, X-ray photoelectron spectroscopy (XPS), and low-energy He ion-scattering spectroscopy (LEIS). The initial heat of adsorption of Ca on MEH-CN-PPV at 300 K is 436 kJ/mol. The heat of adsorption increases to 464 kJ/mol at ∼0.05 ML. We ascribe this initial heat to Ca abstracting cyano groups from the polymer backbone to make Ca(CN) clusters, plus a less important contribution due to Ca abstracting alkoxy groups to make Ca alkoxides. This is supported by XPS which shows the formation of new peaks in the N 1s and C 1s regions consistent with Ca(CN). There is also XPS evidence for Ca reacting with some of the ether groups to make Ca alkoxides at low coverage. Above 0.05 ML Ca coverage, the heat of adsorption decreases nearly exponentially to the sublimation enthalpy of bulk Ca solid (178 kJ/mol) by 5 ML. The observed behavior is attributed to the increasing probability of forming Ca nanoparticles and eventually a continuous solid Ca film on top of the reacted polymer. LEIS, which shows only a slow increase of the signal related to solid Ca, supports this model. Incoming Ca atoms undergo a kinetic competition between diffusing into the polymer to react with subsurface cyano or ether groups and forming or adding to three-dimensional Ca clusters on the surface. For studies done at 130 K, similar behavior is observed, with the heat of adsorption starting lower and decreasing more quickly to the heat of sublimation, already by 1.2 ML Ca coverage. This behavior along with the quicker growth of Ca on the surface of the polymer is attributed to the slower diffusion of Ca adatoms to subsurface cyano and ether groups. The effective thickness of "reacted" polymer (i.e., polymer which has lost its -CN groups and some alkoxy groups) is estimated to be 5.6 nm at 300 K but only 1.0 nm at 130 K. © 2013 American Chemical Society.